From Search to Discovery: Reframing the Consumer Journey in the AI era - Memet Sanjaya (Jurnal Komputer Bisnis, 2026)
The rapid development of artificial intelligence (AI), recommendation algorithms, and social commerce has significantly transformed how consumers discover products in digital environments. Although previous studies have extensively discussed consumer journeys, customer experiences, and AI-enabled marketing, limited attention has been given to explaining how AI reshapes the entry point of the consumer journey. This study aims to develop a conceptual framework explaining the transition from a search-driven consumer journey to a discovery-driven consumer journey. The study adopts a conceptual research design by synthesizing academic literature and recent digital industry reports from Think with Google, We Are Social, and DataReportal. The proposed framework identifies four major digital drivers—artificial intelligence, recommendation algorithms, social commerce platforms, and personalized content—that transform the entry point of consumer interactions from intentional information search to algorithmic product discovery. Furthermore, the framework demonstrates that contemporary consumer journeys have become increasingly platform-mediated, adaptive, and continuous through algorithmic feedback loops. This study contributes to consumer journey literature by proposing algorithmic product discovery as a new conceptual perspective while providing practical implications for organizations seeking to optimize digital marketing strategies in AI-driven environments.